2013
DOI: 10.1155/2013/359217
|View full text |Cite
|
Sign up to set email alerts
|

Determination of NH4+ in Environmental Water with Interfering Substances Using the Modified Nessler Method

Abstract: Nitrogen is an essential element in the environment. If excess nitrogen includingNH4 +is present in water, however, it can result in algae blooming and eventually the destruction of the aquatic ecosystem. Therefore, the determination ofNH4 +in streams, lakes, and effluents of the treatment facilities has long been carried out. The Nessler method is the most common spectrophotometric method to measureNH4 +in water. However, the result of the method becomes inaccurate if there are interfering substances such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 16 publications
1
41
0
1
Order By: Relevance
“…Sulfide concentration was determined by comparing results to standard curve developed with Na 2 S standards. At the same time, the concentration of ammonia in a water sample exposed to the bacterial VMPs for 24 h was measured using modifying Nessler method according to Jeong et al . The absorbance of the samples was measured at 400 nm and compared to standard curve developed with NH 4 Cl.…”
Section: Methodsmentioning
confidence: 99%
“…Sulfide concentration was determined by comparing results to standard curve developed with Na 2 S standards. At the same time, the concentration of ammonia in a water sample exposed to the bacterial VMPs for 24 h was measured using modifying Nessler method according to Jeong et al . The absorbance of the samples was measured at 400 nm and compared to standard curve developed with NH 4 Cl.…”
Section: Methodsmentioning
confidence: 99%
“…Organic C and N were measured using a Perkin -Elmer series II 2400 C and N analyzer. Determination of % N-NH 4 was done by Nessler (Jeong et al, 2013). Colors were defined based on the Munsell Soil Chart, 1975 (Viscarra et al, 2006).…”
Section: Soils Biosolids and Their Mixtures Analysismentioning
confidence: 99%
“…However, nitrite is unstable in the environment and exists at a relatively low concentration in wastewater, limiting the anammox reaction [6,7]. It has been frequently reported that sulfur-based autotrophic denitrification (SAD) can provide nitrite for anammox through the conversion of nitrate into nitrite [8].…”
Section: Introductionmentioning
confidence: 99%